INTRODUCTION TO THE SYMPOSIUM: AN INSTITUTIONAL THEORY OF CULTURAL BIASES, PUBLIC ADMINISTRATION AND PUBLIC POLICY. (December 2016) - 6, PERRI; SWEDLOW, BRENDON
Abstract : This symposium showcases diverse contributions that a particular institutional theory of cultural biases makes to public administration and policy research. Bridging and integrating these subfields, the theory offers powerful explanations for the ways in which institutional processes drive policy‐making. Developed initially by Douglas using Durkheimian theory, Hood and Wildavsky made the theory increasingly influential in public administration and policy. Today, the theory has several variants which nevertheless share common core elements. We briefly survey this institutional theory's contributions to the study of public administration and policy before describing its central claims, analysing the uses of its variants in the symposium articles, and identifying their key advances. We conclude with challenges and promising developments in efforts to conceptualize, operationalize, and test the theory in public administration and policy research.